Experimental Study of a Cu-Mo Alloy Vapor Chamber - Obata, Daniel H. S. [UNESP]; Fukushima, Jeferson C. [UNESP]; Alves, Thiago Antonini; Bazani, Marcio A. [UNESP]; Paschoalini, Amarildo T. [UNESP]; Qaddoumi, N.; Koh, S. K.; Devlin, J. (E D P Sciences, 2016)
In this research, the thermal behavior of a vapor chamber embedded in the base of a heat sink was experimentally analyzed considering the influence of the heat source position. The vapor chamber was produced by a copper and molybdenum alloy with length of 240 mm, width of 54 mm, thickness of 3 mm, and capillary structures composed by copper screen meshes. The working fluid used was de-ionized water. The pure aluminum heat sink was cooled by air forced convection and the evaporator vapor chamber was heated using an electrical resistor simulating integrated circuit power dissipation. The experimental tests were done in a suction type wind tunnel with open return for a heat load varying from 20 to 80 W, for an airflow velocity varying from 1 to 4 m/s, and for three different heat source positions. The experimental results showed that, independently of the heat source position, the considered vapor chamber worked successfully, maintaining low operating temperature.